Pengaruh Penggunaan Aplikasi Google Play Book Terhadap Minat Baca Siswa Kelas VII SMP Negeri 150 Jakarta - Primariz, Elya; Solihati, Nani (Jayapangus Press, 2024)
Reading interest is a person's desire to read without coercion, but currently, students' reading interest is relatively low, which significantly affects the quality of education. One factor contributing to this low interest is technological advancement, which leads them to use smartphones more than reading books. An example of this technological advancement is the Google Play Books application. This study aims to enhance students' understanding and reading interest using the Google Play Books application. Conducted at SMP Negeri 150 Jakarta, the study involved a population of 321 seventh-grade students, with VII-A chosen as the control group and VII-B as the experimental group. The study employed probability sampling with Simple Random Sampling technique for sampling. This quantitative study utilized True Experimental design with Posttest-Only Control Group Design. The research instrument was a questionnaire. Data analysis included Aiken'S V validity test, showing high and very high validity levels. The product moment correlation formula was used for empirical validity testing, indicating valid results. Instrument reliability was tested using Cronbach’s Alpha method, yielding CA (Cronbach's Alpha) = 0.890, indicating high reliability. Normality test results were 0.095 for the experimental group and 0.060 for the control group, while homogeneity was assessed using Levene's statistic, showing homogeneous data distribution. One Way ANOVA test showed a significance level of 0.035, indicating a value less than 0.05. This proves that using the Google Play Books application has an impact on students' reading interest between the experimental and control groups.